Baseline characteristics of the 3,096 patients recruited into the 'Triple Antiplatelets for Reducing Dependency after Ischaemic Stroke' (TARDIS) trial - Bath, Philip M.W.; Appleton, Jason P.; Beridze, M.; Christensen, Hanne; Dineen, Robert A.; Duley, Lelia; England, Timothy J.; Heptinstall, Stan; James, Marilyn; Krishnan, Kailash; Markus, H.S.; Pocock, Stuart J.; et al. (SAGE, 2017)
Background: The risk of recurrence following ischaemic stroke (IS) or transient ischaemic attack (TIA) is highest immediately after the event. Antiplatelet agents are effective in reducing the risk of recurrence and two agents are superior to one in the early phase after ictus.